The effect of channel aspect ratio on flow boiling characteristics within rectangular micro-passages. (February 2022) - Andredaki, Manolia; Vontas, Konstantinos; Georgoulas, Anastasios; Miché, Nicolas; Marengo, Marco
Highlights: High-resolution, 3D, transient, conjugate heat-transfer simulations are performed. The aspect ratio has a significant effect in the generated bubble dynamics. The bubble dynamics are responsible for the resulting heat transfer characteristics. The thermal inertia of the solid domains has a significant role in the overall phenomenon. Conjugate heat transfer simulations are necessary when simulating flow boiling within microchannels. Abstract: In the present paper, a fundamental analysis on the effect of the channel aspect ratio on the bubble dynamics and heat transfer characteristics for the early transient stages of the bubble growth within confined microchannels of rectangular cross-section, under saturated flow boiling conditions, is conducted, utilising high resolution, 3D, transient, conjugate heat transfer simulations. The open-source toolbox OpenFOAM is applied for the simulations, utilising a custom, user-enhanced, diabatic Volume OF Fluid (VOF) solver. Two different series of numerical simulations are performed, focused on a single nucleation event from a single nucleation site and a single nucleation event from multiple, arbitrarily located, nucleation sites, respectively. In each series, three different values of channel aspect ratio are considered, corresponding to a narrow, a square, and a wide microchannel. For the first series, the simulations are performed for a low, a medium, and a high value of applied heat flux and mass flux. For the second series, only the lower values of applied heat flux and mass flux are used for each channel aspect ratio, since this constitutes the worst-case scenario from the overall heat transfer performance point of view, amongst the cases examined in the first series of simulations. The micro-passage aspect ratio has a significant effect in the generated bubble dynamics during the onset of the nucleate boiling regime, as the bubbles grow within the confined liquid crossflow. This alteration of the generated interfacial dynamics, in effect, regulates the size and position of the contact areas of the generated bubbles with the microchannel walls, with a direct effect in the individual contribution and therefore, the balance between the contact line and the liquid film evaporation mechanisms. Moreover, the work presents the quantification of the effect of the solid domain thermal inertia on the whole process and in particular on the local Nusselt numbers. It is evident that considering conjugate heat transfer in numerical simulations of flow boiling is compulsory in order to predict the physical processes in a correct form.